Brief Report: Racial Comparison of D-Dimer Levels in US Male Military Personnel Before and After HIV Infection and Viral Suppression. (15th April 2018) - O'Bryan, Thomas A.; Agan, Brian K.; Tracy, Russell P.; Freiberg, Matthew S.; Okulicz, Jason F.; So-Armah, Kaku; Ganesan, Anuradha; Rimland, David; Lalani, Tahaniyat; Deiss, Robert G.; Tramont, Edmund C.
Abstract : Background: D-dimer blood levels in persons with HIV infection are associated with risk of serious non-AIDS conditions and death. Black race has been correlated with higher D-dimer levels in several studies. We examined the effects of race and HIV on D-dimer over time and the impact of viral load suppression by longitudinally comparing changes in levels among healthy young adult male African Americans and whites before HIV seroconversion and before and after initiation of antiretroviral therapy (ART). Methods: We analyzed D-dimer levels and clinical and laboratory data of 192 participants enrolled in the US Military HIV Natural History Study, a 30-year cohort of military personnel infected with HIV. D-dimer levels were measured on stored sera from each participant at 3 time points: (1) before HIV seroconversion (Pre-SC), (2) ≥6 months after HIV seroconversion but before ART initiation (Post-SC), and (3) ≥6 months after ART with documented viral suppression (Post-ART). Levels were compared at each time point using nonparametric and logistic regression analysis. Results: Compared with whites (n = 106), African Americans (n = 86) had higher D-dimer levels post-SC ( P = 0.007), but in the same individuals, pre-SC baseline and post-ART levels were similar ( P = 0.40 and P = 0.99, respectively). There were no racial differences in CD4 cell counts, HIV RNA viral load, time from estimated seroconversion to ART initiation, and duration on ART. Conclusions: Observed longitudinally, racial differences in D-dimer levels were seen only during HIV viremia. Higher levels of D-dimer commonly observed in African Americans are likely due to factors in addition to race.